2021
DOI: 10.3390/medicina57111178
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Ossicles in the Region of the Foot and Ankle: An Epidemiologic Survey in a Jordanian Population

Abstract: Background and Objectives: The incidence of accessory bones in the region of foot and ankle is quite variable between studies and are often confused with avulsion fractures in trauma patients with musculoskeletal injuries. The aim of this study was to assess the incidence of accessory ossicles of the foot and ankle according to gender, side and coexistence, and to determine how frequently accessory ossicles were misdiagnosed as avulsion fractures. Materials and Methods: Oblique and/or lateral foot radiographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although we reported a high rate of accessory ossicles in our study, we identified at least one accessory ossicle in 52.18% (60/115). In studies in the literature, this rate was reported as 18.3%, 26.1% and 40.2% with different rates (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we reported a high rate of accessory ossicles in our study, we identified at least one accessory ossicle in 52.18% (60/115). In studies in the literature, this rate was reported as 18.3%, 26.1% and 40.2% with different rates (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…This variation should be noted as it may have radiographic appearances similar to a fracture of the posterior talar process (20). Its frequency varies between 1-25% in the literature (7,(14)(15)(16)(17)21). Candan B. et al evaluated the diameters of os trigonum on radiological images and showed its mean length as 10.21 mm and mean width as 6.53 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It is a relatively uncommon anatomical variation, with a reported prevalence of around 0.1 % to 12.5 % in the general population (van Aswegen et al, 2020;Kalbouneh et al, 2021). While often asymptomatic, the os intermetatarseum can be associated with pain and other symptoms that can significantly affect quality of life (de Oliveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The most common accessory bones of the foot and ankle are the os trigonum, the accessory navicular (type 2 is the most common of the three types), and the os intermetatarseum. 3,10 Sesamoids differ anatomically. Sesamoid bones reduce friction and protect tendons; their clinical importance becomes clear during acute trauma or in the differential diagnosis with fractures.…”
mentioning
confidence: 99%
“…The most common accessory bones of the foot and ankle are the os trigonum, the accessory navicular (type 2 is the most common of the three types), and the os intermetatarseum. 3 10…”
mentioning
confidence: 99%